Impact of psychobiotics on anxiety disorder (Research, Society and Development, 2022)
Objective: The objective of this study was to carry out a search for scientific evidence to analyze the impact of psychobiotics in the treatment of anxiety disorder symptoms. Methodology: This is a narrative literature review carried out through a bibliographic search of Portuguese and English articles, available in the Scielo and PubMed/MEDLINE databases. Articles available in full and from the period between 2013 and 2022 were included. The descriptors used were: “Probiotics”, “Anxiety”, “Probiotics” and “Anxiety”. Results: The brain and gut form a two-way communication axis, and information can be generated both at the gut and brain level, popularly known as the microbiota-gut-brain axis, which can be directly or indirectly related to certain psychological disorders such as anxiety. Indicators indicate that therapies capable of modulating the microbiota can alleviate symptoms of anxiety, with an inadequate diet and poor in nutrients being a risk factor for this pathology. Thus, studies have shown that supplementation with probiotics (psychobiotics), especially Lactobacillus and Bifidobacterium species, combined with a balanced diet, has shown positive results. Final considerations: It is concluded that the psychobiotics of the Lactobacillus and Bifidobacterium classes have a positive impact on the treatment of anxiety symptoms. In this way, psychobiotic supplementation is presented as a complement to the treatment of anxiety and the importance of a balanced diet in conjunction with probiotic supplementation for physical and psychological health is evident.